Refined methods of calculating the switching overvoltage in semiconductor AC devices - Soskov, Anatoly; Sabalaeva, Natalia; Glebova, Marina; Forkun, Yana (Eastern-European Journal of Enterprise Technologies, 2016)
The study focuses on switching overvoltage applied to semiconductor switches of semiconductor AC devices at the moment of switching electric circuits owing to the energy that has accumulated in the inductive elements of the mains and a disconnectable load. Since the cost of power semiconductor devices is determined both by the current with which they are compatible and the class of the device that determines the amount of blocked voltage, it is important to use special measures that would reduce the voltage and make it closer to that of the network. Usually, the voltage is reduced with the help of protective RC-circuits and nonlinear surge suppressors (varistors). The aim of the research was to refine the methods of calculating the switching overvoltage and parameters of protection circuits in semiconductor devices with account for the diversity of semiconductor switches and their dynamic characteristics since the current methods of calculation do not fully account for them and, therefore, are not fully precise. The newly developed methods of calculating the switching surge consider dependence of the reverse recovery of power semiconductor devices on the rate of current decline in their circuit as well as high resistance of modern semiconductor devices to the effect of ultra-high voltage slew rates. The methodology also takes into account the conditions of the load switching with the help of these devices. The developed methodology of selecting parameters for the RC-protective circuit accounts for the nature of any switching transients and significantly extends the range of protective circuit parameters. The proposed surge suppressor for semiconductor AC switching devices is additionally supplied with a varistor that is connected in parallel to the RC-circuit, which allows a significant reduction in the capacitance of the circuit condenser and the leakage current and approximately 30% reduction in the rate of switching surges. This would greatly reduce the class of power semiconductor devices.